Effect of powder calcination on the sintering of hydroxyapatite - Tan, C.Y.; Ramesh, S.; Aw, K.L.; Yeo, W.H.; Abd Shukor, Mohd Hamdi; Sopyan, I. (Malaysian Medical Association, 2008)
The sintering behaviour of synthesized HA powder that was calcined at various temperatures ranging from 700 degrees C to 1000 degrees C was investigated in terms of phase stability, bulk density, Young's modulus and Vickers hardness. The calcination treatment resulted in higher crystallinity of the starting HA powder. Decomposition of HA phase to form secondary phases was not observed in all the calcined powders. The results also indicated that powder calcination (up to 900 degrees C) prior to sintering has negligible effect on the sinterability of the HA compacts. However, powder calcined at 1000 degrees C was found to be detrimental to the properties of sintered hydroxyapatite bioceramics.